2014
DOI: 10.1111/1755-0998.12332
|View full text |Cite
|
Sign up to set email alerts
|

Performance of partial statistics in individual‐based landscape genetics

Abstract: Individual-based landscape genetic methods have become increasingly popular for quantifying fine-scale landscape influences on gene flow. One complication for individual-based methods is that gene flow and landscape variables are often correlated with geography. Partial statistics, particularly Mantel tests, are often employed to control for these inherent correlations by removing the effects of geography while simultaneously correlating measures of genetic differentiation and landscape variables of interest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 56 publications
6
90
0
Order By: Relevance
“…Our study demonstrates that combining ordination and regression statistics with simulations to quantify errors can help disentangle potential errors from landscape effects on gene flow in an individual-based framework. RDA and spatially lagged regression did not require calculation of connectivity indices (Kierepka and Latch, 2015), which was critical for this study given the nearly complete lack of relevant life history data. With simulations, we were able to quantify the confounding effects of spatially biased sampling to separate type I errors from biologically relevant landscape effects on gene flow.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study demonstrates that combining ordination and regression statistics with simulations to quantify errors can help disentangle potential errors from landscape effects on gene flow in an individual-based framework. RDA and spatially lagged regression did not require calculation of connectivity indices (Kierepka and Latch, 2015), which was critical for this study given the nearly complete lack of relevant life history data. With simulations, we were able to quantify the confounding effects of spatially biased sampling to separate type I errors from biologically relevant landscape effects on gene flow.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a partial RDA, a constrained ordination technique that is the multivariate analog to simple linear regression (Legendre and Legendre, 1998). Previous simulation studies in both population- (Fortín and Legendre, 2010) and individual-based (Kierepka and Latch, 2015) studies have demonstrated that RDA has much greater power than Mantel tests to detect relationships in autocorrelated data. In individual-based studies, however, RDA can suffer from type I errors (that is, false significance; Kierepka and Latch, 2015), so additional steps are needed to control for any potential errors.…”
Section: Landscape Genetic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Mantel tests remain common in landscape genetics (Manel et al., 2003) and can perform better than other methods when the assumption of linearity is not violated (Kierepka & Latch, 2015; Shirk, Landguth, & Cushman, 2017; Zeller et al., 2016). However, use of Mantel tests is controversial because of weakness in accounting for spatial autocorrelation (Legendre & Fortin, 2010; Manel et al., 2003), so we interpret results of the partial Mantel test with caution and as a supplement to the results of the MMRR.…”
Section: Methodsmentioning
confidence: 99%